2021
DOI: 10.1523/jneurosci.1895-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Regulation of Cortical Processing Speed via Gain Modulation

Abstract: To thrive in dynamic environments, animals must be capable of rapidly and flexibly adapting behavioral responses to a changing context and internal state. Examples of behavioral flexibility include faster stimulus responses when attentive and slower responses when distracted. Contextual or state-dependent modulations may occur early in the cortical hierarchy and may be implemented via top-down projections from corticocortical or neuromodulatory pathways. However, the computational mechanisms mediating the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 117 publications
(213 reference statements)
0
25
0
Order By: Relevance
“…These baseline changes may be driven by top-down projections from higher cortical areas or by neuromodulators. In a recurrent circuit exhibiting attractor dynamics, changes in baseline levels modulate the average transition times between metastable attractors ( Mazzucato et al, 2019 ; Wyrick and Mazzucato, 2021 ). In these models, attractors are represented by potential wells in the network’s energy landscape, and the height of the barrier separating two nearby wells determines the probability of transition between the two corresponding attractors (lower barriers are easier to cross and lead to faster transitions, Figure 4B ).…”
Section: Contextual Modulation Of Temporal Variabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…These baseline changes may be driven by top-down projections from higher cortical areas or by neuromodulators. In a recurrent circuit exhibiting attractor dynamics, changes in baseline levels modulate the average transition times between metastable attractors ( Mazzucato et al, 2019 ; Wyrick and Mazzucato, 2021 ). In these models, attractors are represented by potential wells in the network’s energy landscape, and the height of the barrier separating two nearby wells determines the probability of transition between the two corresponding attractors (lower barriers are easier to cross and lead to faster transitions, Figure 4B ).…”
Section: Contextual Modulation Of Temporal Variabilitymentioning
confidence: 99%
“…In particular, a decrease (increase) in pyramidal cells gain can lead to faster (slower) average action timing. This biologically plausible computational mechanism was proposed to explain the acceleration of sensory coding observed when gustatory stimuli are expected compared to when they are delivered as a surprise ( Samuelsen et al, 2012 ; Mazzucato et al, 2019 ); and the faster encoding of visual stimuli observed in V1 populations during locomotion periods compared to when the mouse sits still ( Wyrick and Mazzucato, 2021 ). Transition rates between attractors may also be modulated by varying the amplitude and color of the fluctuations in the synaptic inputs (see Appendix 3), while keeping the barrier heights fixed.…”
Section: Contextual Modulation Of Temporal Variabilitymentioning
confidence: 99%
See 3 more Smart Citations